Analisis Efektivitas Line Proses Fly Wheel, Presure Plate 2/1 dan Presure Plate 1/1 dengan Metode Overall Resource Effectiveness (ORE) di PT. Braja Mukti Cakra - Madani, Muhammad Aqshal; Sudarwati, Wiwik (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. Braja Mukti Cakra (BMC) is a manufacturing company specialising in engine components, clutches, brakes, axles, and undercarriages for cars and trucks. PT. BMC has 57 process lines, and three of these process lines do not meet the production target based on data from the Production Department for January to August 2022—namely, the Fly Wheel line process, Pressure Plate 2/1, and Pressure Plate 1/1. After calculating the effectiveness value using Overall Resource Effectiveness (ORE), there are still many ORE values below 85% or not optimal, and some are in the range of 40% to 60%, indicating the need for further improvement. After being explained using a fishbone diagram, there are four causal factors: humans, machines, materials, and method/tool designs. When the cause of the problem is known, a 5W + 1H analysis is conducted to identify and address the root causes of the issues that arise. So that the performance of the production process in the three is more effective